Operator Role In Front Office Department On Handling Guest Requests At Harris Resort Barelang - Dame Afrina Sihombing; Kezia Hirano Danito (Universitas Internasional Batam, 2021)
Harris Resort Barelang Batam is categorized as a four-star hotel, and managed by Tauzia group. Author had the opportunity to practice for four months in Front Office Department as ‘Harris Button Operator’. Front Office Department is the first and last department that guest meet, so it has responsibility to give a good impression and experience to the guest during their stay. As ‘Harris Button’ Operator, author should complete all guest requests using only by audio, in this case, the operator need to be competent in handling each guest request or handle any problem and could solve it in a timely manner. On-the-job training gave the author opportunity to implement the theory to the work field and practice it directly. The author also received a lot of knowledge and the ability to solve problems between guest and co-workers. The data for this research is conducted by interview to extract information from several sources and by observation from the field. The purpose of this research is to give the readers and future researchers knowledge about hotel industry, especially in Front Office Department.